The Relationship Between Sprint Running and Long Jump Results in Class X Students of SMK Negeri 1 Simpang Ulim - Tonara, Arda; Prayetno, Bambang Eko (Literacy: Journal of Education and Social Science, 2024)
This study aims to determine the relationship between sprint running speed and long jump ability among Grade X students of SMK Negeri 1 Simpang Ulim. The population of this study consisted of all Grade X students of SMK Negeri 1 Simpang Ulim, totaling 150 students. Given the relatively large population, the researcher took 20% of the total population as a sample, amounting to 30 students, using a random sampling technique. Data collection in this study involved measuring sprint running speed using a 50-meter sprint test and long jump ability using a long jump test. Data analysis was conducted using correlational statistical techniques.The data analysis results showed that the average sprint running speed of Grade X students at SMK Negeri 1 Simpang Ulim was 49.98, with a standard deviation of 0.83, and the average long jump ability was 50.10, with a standard deviation of 10.07. The correlation calculation resulted in a value of 0.41. To test the hypothesis, the t-test was used, and the calculated t-value was 2.42, which is greater than the critical t-value of 2.05553. Thus, it can be concluded that there is a relationship between sprint running speed and long jump results among Grade X students at SMK Negeri 1 Simpang Ulim. In other words, the hypothesis is accepted. It is recommended that physical education teachers emphasize that muscle strength, speed, and power are key supporting factors in athletic sports, particularly in the long jump event. Teachers should pay more attention to and provide training to improve students' long jump performance.